Epidermal growth factor receptor determination on tumour imprints. Issue 2 (February 1993) - Hastrich, D J; Dunn, J M; Newcomb, P; Hall, P; Rooney, N; Nicholson, S; Farndon, J R
Abstract : Epidermal growth factor receptor (EGFR) is a sensitive prognostic indicator in women with breast cancer. A new technique for the detection of EGFR on breast cancer imprints is described and evaluated in relation to immunohistochemistry on frozen sections. The standard streptavidin-biotin method using the R1 antibody on frozen sections was modified for use on tumour imprints. In the first group (group 1 imprints) 43 tumours were assessed by frozen section and imprint staining. The group 1 imprint method had a sensitivity of 50% and a specificity of 89% compared with the frozen sections. Further modifications were made for the following 32 tumours (group 2) and this method had a much improved sensitivity of 94% while specificity was preserved. This method is simple and could be performed in any hospital histopathology department.